The Strategy of Inclusive Classroom Learning (ICL) and Communicative Language Teaching (CLT) for Class X Students in the Govt. High Schools under Khagarijan Block of Nagaon District, Assam - Dr. Parbin Sultana, Lina Saikia (South Eastern European Journal of Public Health, 2025)
Inclusive Classroom Learning (ICL) and Communicative Language Teaching (CLT) are the challenging inclusions in the educational disciplines to standardize, modify, and universalize the ongoing education system, directed by NEP 2020 recently. According to this policy, inclusive classrooms may provide equal opportunity to every child irrespective of their physical, mental, social, and emotional capabilities. On the other hand, CLT will provide interactive and spontaneous learning and foster a joyful and productive educational environment. In high schools, especially the students of class X need special attention for their physical and mental growth, educational competence and maturity so that they can smoothly transact themselves from the secondary level to a higher level where hurdles and life challenges are waiting for them. In this paper, the researchers aim to highlight the activities or practices on the mentioned ground done for class X students in the Govt. schools of Nagaon Town (Khagarijan Block). An Interactive Method is selected to process this minor research paper. However, observation would also be done wherever possible within a limited time.